Sleep hygiene sebagai moderator dalam hubungan antara psychological distress dan sleep quality - Alya Chandrika; Devie Yundianto (Cognicia, 2026)
This study aims to analyze the effect of psychological distress on sleep quality among workers and to examine the role of sleep hygiene as a moderating variable. The approach used is a quantitative method with a cross-sectional design. The study sample involved 162 workers in the Jakarta, Bogor, Depok, and Tangerang areas, selected using convenience sampling. Variable measurements were conducted using the Pittsburgh Sleep Quality Index (PSQI), Sleep Hygiene Practice Scale (SHPS), and Kessler Psychological Distress Scale (K10). Data analysis included partial t-tests to identify relationships between variables and interaction tests to assess moderating effects. The study results indicate that psychological distress has a negative and significant effect on sleep quality (β = 0.392; p < 0.05). This means that the higher the level of psychological distress, the lower the individual’s sleep quality. In addition, sleep hygiene was also found to have a positive and significant effect on sleep quality, but it did not act as a moderator in the relationship between psychological distress and sleep quality. These findings confirm that the implementation of healthy sleep practices can help improve sleep quality, but cannot completely mitigate the negative impact of psychological distress on sleep quality.